Penerapan Digital Marketing Funnel pada Kampanye Kemanusiaan: Studi Komparasi Aktivitas Media Sosial YAUM, DT Peduli, dan BAZNAS - Muhammad Farizan Saputera; Lutfi Adji Ardiansyah; Mulharnetti Syas (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
The rapid advancement of digital technology has fundamentally transformed the landscape of humanitarian fundraising, requiring philanthropic institutions to adopt structured communication strategies to remain competitive in the attention economy. This study aims to analyze the application of the digital marketing funnel through Content Marketing strategies in three Islamic philanthropic institutions based in Cirebon: YAUM, DT Peduli Cirebon, and BAZNAS Kota Cirebon. Employing the Quantitative Content Analysis method, this study systematically observed and coded all social media posts published on Instagram and TikTok over a 14-day period (November 27 – December 10, 2025). A total of 145 content units were analyzed and categorized based on four funnel stages: Awareness (Education & Inspiration), Consideration (Program Information), Conversion (Fundraising), and Retention (Reports & Transparency). Intercoder reliability was established using Krippendorff’s Alpha (α = 0.85). Results indicate that YAUM dominated share of voice with an average of 6.4 posts per day, applied a proactive Always-On funnel strategy, and demonstrated the most complete funnel coverage across all four stages. DT Peduli showed moderate funnel activity concentrated at the top and middle stages, while BAZNAS exhibited a reactive event-riding pattern, activating only at the bottom-of-funnel during the Sumatra/Aceh natural disaster. The absence of top-of-funnel content by BAZNAS prior to the crisis period significantly limited its potential for long-term donor Retention. This study recommends that Islamic philanthropic institutions adopt a structured content calendar, implement content localization strategies for branch-level communications, and expand to multi-platform (omnichannel) strategies to optimize donor acquisition and Retention.